Selective isolation and genomic characterization of biopolymer producer—a novel feature of halophile Brachybacterium paraconglomeratum MTCC 13074 - Teja Mandragutti; G. Sudhakar (Journal of Genetic Engineering and Biotechnology, 2023)
Abstract Background Biopolymers like polyhydroxyalkanoates (PHA) are the best natural macromolecules to use as alternative to the synthetic polymers. Many prokaryotes accumulate PHA as cytoplasmic intracellular granules and their accumulation is triggered by starving conditions. The PHAs are ecofriendly and used to create biodegradable plastics. The microbial synthesized PHA had acquired global importance in industrial and biomedical sectors. Results Ten different bacterial strains were isolated for the screening of PHA producers from the estuarine region of the Bay of Bengal, Suryalanka in Bapatla. A yellowish slimy circular colony known as M4 is actively growing on selective minimal media and was screened for polymeric granules in its cytoplasm using Sudan Black B and confirmed with the fluorescent dye Nile blue A. All of the isolates were biochemically tested and isolate M4 is the most capable of growing at high NaCl concentrations (3.2 percent) and tests positive for catalase, methyl red. The M4 strain revealed clear hydrolysis of gelatin, starch, and casein. The 16S rRNA sequencing revealed that M4 is 99.72% of identity to Brachybacterium paraconglomeratum LMG 19861(T) in BLAST and the obtained strain was assigned with accession no. MTCC 13074 and deposited in NCBI with accession no. MW899045. The chief cellular fatty acids found in M4 were C14:0, C15:0, C16:0, C18:1cis-9, C18:0, iso-C15: 0, iso-C14: 0, anteiso-C17: 0 and C18:1-7. Crotonic acid formation from M4-PHB extract was detected at 235nm in a UV spectrophotometer. Methanolysis was done, and derivatives of polyhydroxybutyric acid (PHB) in the extract were analyzed using GC-MS. Increasing viscosity was seen in the extracts which confirms the presence of polymer in the extracts. Thermogravimetric analysis was studied to determine the thermal profile of the PHB in the extract of M4. Conclusion In the study, the selective screening and extraction of ecofriendly PHB from M4 strain was highlighted. Brachybacterium paraconglomeratum is a novel strain showed its uniqueness by producing few monomeric derivatives of PHB. The strain was reporting for the first time as PHA producer. B. paraconglomeratum has promising characteristics according to its metabolic profile. In addition, this study also helps to understand the diversity of bacteria isolated from marine sources.